Acid demineralization with pyrite removal and critical point drying for kerogen microstructural analysis. (1st October 2019) - Sun, Tao; Bake, Kyle D.; Craddock, Paul R.; Gunawan, Bryan; Darnell, Larry M.; Bissada, Kadry K.; Pomerantz, Andrew E.
Highlights: Novel method to preserve both chemical & microstructural properties of kerogen. Combines closed-system acid-demineralization & critical point drying procedures. Method enables study of oil & gas storage and transport in kerogen-hosted porosity. Abstract: Hydrocarbon storage and transport in unconventional shale resources occurs predominantly within pores hosted by kerogen (solid and insoluble organic matter in sedimentary rocks). Kerogen-hosted pores are small, so physiochemical interactions between pore fluids and pore surfaces (e.g., adsorption) are particularly important in shale. The understanding and prediction of hydrocarbon storage and transport in shale is dependent, therefore, upon the correct understanding of both chemical composition and pore geometry of kerogen. Several recent studies have attempted to construct molecular models of kerogen physical and/or chemical structure. Developing these models is challenging, in part because of the lack of laboratory samples of kerogen for experimental characterization that preserve both its chemical and microstructural properties representative of those in the subsurface. This study presents an integrated kerogen-isolation procedure that combines closed-system chemical demineralization with pyrite removal and critical point drying. The method produces a kerogen that is not only high in chemical purity but more representative of kerogen microstructure that occurs in the subsurface. Characterization of kerogen microstructure, which can be performed by direct measurement of the isolate obtained by this procedure, is essential to better understand and predict the storage, transport, and production hydrocarbons from unconventional resources.